Quarterlife Crisis in Batak Women Entering the Emerging Adulthood Period: and What is the Role of Self-Concept and Social Support in It? - Dwi Septi Aryani; Raras Sutatminingsih; Rahma Fauzia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Quarterlife crisis is a phenomenon that makes an individual confused about how to live their life in the future. Confused about fulfilling his developmental duties. A quarterlife crisis can cause a variety of stresses and anxieties including worries about career achievements, financial opportunities, increased competition between members of a group, the rise of psychological issues, and fear of relationships. This causes stress, anxiety, and even depression. There are feelings of anxiety, pessimism, low self-esteem, helplessness. This study aims to determine the influence of self-concept on quarterlife crisis moderated by social support for Batak women entering the emerging adulthood. This research used the quantitative method. This study involved 272 Batak women entering the emerging adulthood. The measuring instruments used in this research are quarterlife crisis, self-concept, and social support scale. Data in this research were analyzed using simple regression analysis and moderated regression analysis methods. The result show that self-concept has a negative and significant effect on the quarterlife crisis among Batak women entering the emerging adulthood the value is -572 with significant .000. This means that higher the self-concept, than lowest the quarterlife crisis among Batak women entering the emerging adulthood. The second result is social support moderated the effect of self-concept on the quarterlife crisis the significant is .047. This means that social support strengthens or weakens the influence of self-concept on quarterlife crisis.Quarterlife crisis adalah fenomena yang membuat seorang individu mengalami kebingungan untuk menjalani kehidupannya ke depan. Bingung untuk memenuhi tugas perkembangannya. Adanya tekanan dan kecemasan meliputi peluang finansial, kebimbangan atas pencapaian karier, meningkatnya persaingan antar anggota dalam suatu kelompok, maraknya isu-isu psikologi, serta ketakutan menjalin hubungan merupakan dampak yang akan dirasakan pada saat seorang individu mengalami quarterlife crisis. Hal ini menimbulkan respons stres, cemas, bahkan depresi. Pada saat mengalami quarterlife crisis akan muncul perasaan gelisah, pesimis, rendah diri dan tak berdaya. Penelitian ini bertujuan untuk mengetahui pengaruh konsep diri terhadap quarterlife crisis dimoderasi oleh dukungan sosial pada wanita suku Batak yang menginjak masa emerging adulthood. Penelitian ini menggunakan metode kuantitatif. Penelitian ini melibatkan 272 wanita suku Batak yang menginjak masa emerging adulthood. Skala quarterlife crisis, konsep diri dan dukungan sosial merupakan alat ukur yang digunakan pada penelitian ini. Data dalam penelitian ini dianalisis dengan menggunakan regresi sederhana dan regresi moderasi. Hasil penelitian menunjukkan bahwa konsep diri berpengaruh negatif dan signifikan terhadap quarterlife crisis pada wanita suku Batak yang menginjak masa emerging adulthood nilainya adalah -572 dengan signifikansi .000. Ini berarti semakin tinggi konsep diri maka semakin rendah quarterlife crisis pada wanita suku Batak yang menginjak masa emerging adulthood. Hasil kedua adalah dukungan sosial memoderasi pengaruh konsep diri terhadap quarterlife crisis dengan nilai signifikansi .047 Artinya dukungan sosial memperkuat atau memperlemah pengaruh konsep diri terhadap quarterlife crisis.